Pemetaan Jalur Evakuasi Bahaya Banjir Bandang di Nagari Bukik Batabuah dan Nagari Batu Taba Kabupaten Agam - Amril, Mohammad Rizki; Edial, Helfia (Lembaga Yasin AlSys, 2025)
Nagari Bukik Batabuah and Nagari Batu Taba in Agam Regency are highly vulnerable to flash floods due to their location on the slopes of Mount Marapi and high rainfall intensity. The flash flood that occurred in 2024 caused severe losses, including casualties and infrastructure damage, while the absence of clearly defined evacuation routes hindered rescue efforts. This study aims to design effective evacuation routes using Geographic Information Systems (GIS) to minimize future disaster risks. A mixed-methods approach was employed, with a dominant qualitative orientation in which researchers were directly involved in field data collection. The results indicate that the high-risk hazard zone covers 104.79 hectares, medium risk 1,158.27 hectares, and low risk 1,158.94 hectares. Recommended evacuation points in Nagari Bukik Batabuah include SDN 08 Kubang Duo Koto Panjang, SDN 11 Batabuah Koto Baru, the Bukik Batabuah Village Office, and Masjid At Taqwa Mantuang. In Nagari Batu Taba, the central evacuation point is SMKN 1 Ampek Angkek. Potential evacuation routes include Jl. Raya Canduang, Jl. Raya Sungai Pua, and Jl. Raya Panca. These findings provide a crucial foundation for disaster risk mitigation efforts and for strengthening community preparedness in disaster-prone areas.